Islamic Authority Figures and Their Religioscapes in Indonesia - Claudia Seise (Teosofia: Indonesian Journal of Islamic Mysticism, 2021)
In this article I argue that religious authority figures in Indonesia form the core of any given religioscape. A religioscape is a dynamic social space where one religious practice or religious interpretation is predominant. At the same time religious authority figures are influenced by the historically grown religioscape in which they live, and this mutual process affects all the people living in it. With the example of three religious authority figures and their respective learning institutions in Indonesia, I aim to illustrate how Muslim personalities influence and shape the religioscape that surrounds them. The first case study is grounded in the mystic Islam found in Yogyakarta, the second case study explores the mixture of local and Hadhrami influences in the Islamic practice of South Sumatra, while the third case study examines an imported form of reform Islam in a transmigrasi settlement. Of major importance in these case studies will be what influences the religious authority figures and what tools are used to disseminate their thoughts and interpretations of Islam. I argue that the concept of the religioscape enables us to better understand the impact that religious authority figures have on their surroundings and vice versa. It can also serve as a methodological tool to grasp the diverse plurality of Islamic practices in Indonesia.